Qur'anic Exegesis in the Era of Artificial Intelligence: Religious Authority, Digital Polarization, and Religious Moderation in a Pluralistic Society - Hamdan, Ali (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract This article examines the transformation of religious authority, digital polarization, and religious moderation within pluralistic societies. This qualitative research employs a literature review and thematic-contextual interpretation (tafsir). The data sources for this study include Qur'anic verses, exegetical literature, research on artificial intelligence, digital religion, religious authority, social media polarization, and religious moderation. The findings indicate that AI can assist in verse searching, linguistic analysis, thematic classification, and expanding Islamic knowledge. However, AI has several shortcomings, such as data bias, a lack of contextual understanding, and an absence of moral responsibility. Furthermore, AI can fragment religious authority and accelerate the dissemination of exclusive interpretations through algorithms, misinformation, and digital echo chambers. Consequently, AI should be regarded as an auxiliary tool, not a replacement for Islamic scholars (ulama) or exegetes (mufassir). To steer the use of AI towards justice, tabayun (verification/cross-checking), discussion, respect for differences, and public welfare (maslahah), thematic-contextual interpretation and the principles of religious moderation are essential. Keywords: Artificial Intelligence; Digital Polarization; Religious Moderation; Qur'anic Exegesis; Religious Authority.   Abstrak Artikel ini membahas bagaimana otoritas keagamaan berubah, polarisasi digital, dan moderasi agama dalam masyarakat majemuk. Penelitian ini adalah penelitian kualitatif yang menggunakan studi kepustakaan dan tafsir tematik-kontekstual. Ayat-ayat Al-Qur'an, literatur tafsir, penelitian kecerdasan buatan, religi digital, otoritas keagamaan, polarisasi media sosial, dan moderasi beragama adalah sumber data penelitian. Hasil penelitian menunjukkan bahwa AI dapat membantu dalam pencarian ayat, analisis bahasa, klasifikasi tema, dan memperluas pengetahuan Islam. Meskipun demikian, AI memiliki beberapa kelemahan, seperti bias data, tidak memahami konteks, dan tidak memiliki tanggung jawab moral. Selain itu, AI dapat memperpecahkan otoritas keagamaan dan mempercepat penyebaran tafsir eksklusif melalui algoritma, misinformasi, dan ruang gema digital. Akibatnya, AI harus dianggap sebagai alat bantu, bukan pengganti ulama atau mufasir. Untuk mengarahkan penggunaan AI ke arah keadilan, tabayun, diskusi, penghormatan terhadap perbedaan, dan kemaslahatan masyarakat, diperlukan interpretasi tematik-kontekstual dan prinsip moderasi beragama. Kata Kunci: Kecerdasan buatan; Moderasi beragama; Otoritas keagamaan; Polarisasi digital; Tafsir Al-Qur’an.